The "sons of god" in Genesis 6:1-4 - Siqueira, Reinaldo W. (Kerygma, 2005)
Genesis 6:1-4 is usually considered as an obscure passage difficult of interpretation. Many consider it as a mythological account depicting the marriage of angels, or other celestial beings, with women. Others see in it a narrative that describes the violence and abuse of power practiced by kings and powerful rulers in the world before the Flood. A third group interprets this passage as an account narrating the apostasy of men of the Sethite lineage when they united themselves in marriage with women from the Cainite family. The present study approaches the text from the perspective of the Close Reading Method. It finds in the literary context, in the text’s structure, in the sequence of the narrative in Genesis 4-6, and in the themes and words that are used support for the interpretation of the "sons of Gods" as men from the Sethite lineage and the "daughters of man" as women from the Cainite family.